Pengaruh Brain Gym terhadap Konsentrasi Belajar - Suratun Suratun; Sri Tirtayanti (Jurnal Keperawatan Muhammadiyah, 2020)
Learning concentration is the ability to focus attention on the lesson.Â  Concentration is focused on the content of learning materials and the process of obtaining them. To strengthen attention to the lesson, the teacher needs to use a variety of teaching-learning strategies, and take into account study time and interlude breaks. According to research, exercise and exercise at Brain Gym can have a positive influence on increasing concentration, attention and the ability of brain function to plan, respond and make decisions. This study aims to analyze the effect of the brain gym on the concentration of student learning. Using true experiment design with the Pretest-Posttest control group design approach. The sampling technique uses purposive sampling, amounting to 32 respondents. The results of the paired t-test in the intervention group showed that there were differences in the level of concentration before and after doing a brain gym with a value of p = 0.00 measurement I, p = 0.007 measurement to III and there was no difference in measurement II p = 0.240. Whereas in the control group there were differences in the concentration level at the measurement of 1 p = 0.002 and there was no difference in the measurement II p = 0.319 and III p = 0.168. and there are significant differences between the intervention and control groups. Brain Gym is a series of simple movement exercises to help the brain function better during the learning process. Simple physical exercise helps blood flow to the brain and can help improve the learning process by ensuring the brain remains alert. A brain gym can be developed at school to help students improve their concentration in learning.